Endovenous heat-induced thrombosis after ablation with 1470 nm laser: Incidence, progression, and risk factors. (June 2015) - Sufian, S; Arnez, A; Labropoulos, N; Lakhanpal, S
Objectives: To evaluate the incidence of heat-induced thrombosis, its progression and risk factors that may contribute to its formation after endovenous laser ablation. Methods: This was a prospective evaluation of all patients who had endovenous laser ablation of the great saphenous vein, accessory saphenous vein, and small saphenous vein using 1470 nm wavelength laser, from March 2010 to September 2011. All patients who developed endovenous heat-induced thrombosis at the saphenofemoral junction or at the saphenopopliteal junction were included. Demographic data, history of venous thrombosis, body mass index, vein diameter, reflux time, catheter tip position, endovenous heat-induced thrombosis progression, number of phlebectomies, and venous clinical severity scores were analyzed. Duplex ultrasound was done in all patients preoperatively, and 2–3 days postoperatively. Results: Endovenous laser ablation was performed in 2168 limbs. Fifty-seven percent had great saphenous vein, 13% accessory saphenous vein, and 30% small saphenous vein ablation. Endovenous heat-induced thrombosis was developed in 18 limbs (12 at saphenofemoral junction and six at saphenopopliteal junction) for an incidence of 0.9%. Eight were class 1 and 10 were > class 2. No pulmonary embolism was reported. The percentage of men with endovenous heat-induced thrombosis was higher compared to those without (39% vs. 24%, p = .14). The median age for endovenous heat-induced thrombosis patients was 59.6 compared to non-endovenous heat-induced thrombosis ( p = .021). Great saphenous vein/accessory saphenous vein diameter for endovenous heat-induced thrombosis patients was 8.0 mm versus 6.3 mm for non-endovenous heat-induced thrombosis patients ( p = .014), and for small saphenous vein it was 5.7 mm versus 4.5 mm ( p = .16). Multiple concomitant phlebectomies were performed in 55.6% of the endovenous heat-induced thrombosis patients compared to 37% in non-endovenous heat-induced thrombosis ( p = .001). All other parameters were similar between endovenous heat-induced thrombosis and non-endovenous heat-induced thrombosis group. Endovenous heat-induced thrombosis resolution occurred in 16 cases at 2–4 but two cases progressing from class 1 to 2, before resolution. The mean VCSS score for endovenous heat-induced thrombosis patients preoperatively was 5.6 and improved to 2.8 ( p = .003) at one month. Conclusion: Risk factors associated with endovenous heat-induced thrombosis formation after endovenous laser ablation include: vein size, age, and multiple phlebectomies. Endovenous heat-induced thrombosis resolves in 2–4 weeks in most patients but it may worsen in few.